大众宗教复兴的政治 ：庙宇、国家和跨境宗教网络 = The politics of revitalizing popular religious : temple, state, and trans-boundary religious networks - Qu, Xiaolei (Nanyang Technological University, 2017)
本论文是对当代中国大众宗教政治的一项跨学科研究。在改革开放之前，位于厦门和漳州（中国东南沿海的两个地级市）的青礁慈济东宫和白礁慈济宫，均被转化为生产场所，而慈济北宫和慈济南宫则被夷为平地。随着 1970 年代末改革时期的到来，各类宗教现象以惊人的速度和规模再现。青礁慈济东宫和白礁慈济宫在八十年代末均开始重修，而慈济北宫直到 1994 年才开始重建，慈济南宫直到如今仅恢复为一座无门的小庙。基于在厦门和漳州共计 12 个月的田野调查，本研究强调国家和跨境宗教精英在中国大众宗教不均衡复兴中的角色。本文提出四个主要论点。其一，对宗教竞争进行了明确定义。通过考察国家力量在白、青礁慈济宫宗教竞争中的角色，反驳了宗教经济理论的论断——国家管控宗教市场导致宗教竞争性下降，宗教活力降低。多种国家力量的存在，国家力量统筹庙宇资源的考量，国家与宗教关系基于不同时空的多种模式，以及社会经济背景因素，使得国家与宗教竞争的关系复杂化。换句话说，国家力量的参与与宗教竞争并不是确定化的相反关系。其二，通过动员宗教实践、群体，厦门出现的对大众宗教管控与赞助相结合的方式，展现了中国政府执政合法性如何通过多功能的工程得到了增强——发展宗教旅游经济、参与宗教内部竞争、促进与台湾的政治统一，同时展现了基层政府重构的治理方式具有吸纳“权 利的文化网络”的潜力。另外，福建的例子表明，当代中国宗教复兴过程中的一个重要转变，便是至少在一部分庙宇中，出现了弥散性宗教的“部分制度化”，特别是“组织制度化”现象。“现代性”国家力量的直接组织介入或间接政策要求，是转变的重要推动因素之一。其三，保生慈济文化节和保生大帝台湾巡游活动表明，某些大众宗教实践已经被顺利地嵌入到了国家政治象征体系，作为“想象”甚至“可视化”民族国家的重要方式。其四，研究指出国家与台湾跨界宗教精英之间存在一种 “不均衡的共生关系”。 This dissertation is an interdisciplinary account of politics of temple -based popular religion in contemporary China. Before the reform era, both the Eastern and Western Temples were transformed into productive physical spaces, whereas the Northern and Southern Temples were torn down completely by villagers. Then, an astounding resurgence of religion took place with the onset of economic reform and ideological relaxation in the late 1970s. While both the Eastern and Western Temples have enjoyed a tremendous period of revival in the late 1980s, it was not until 1994 that villagers from the Wencuo Village began to reconstruct the Northern Temple on the site where it had once stood. The Southern Temple, one of the oldest Ciji temples, is now a dilapidated, deserted temple that does not even have a door. Based on a total of 12 months of fieldwork conducted in Xiamen and Zhangzhou, this study highlights the roles that Chinese state and trans-boundary religious activists have played in the uneven revival of popular religion. It presents four major arguments. First, the religious economy model argues that the relation between state regulation and religious competition and vitality is inverse. In contrast to the religious economy model that adopts a reductionist approach to the role of the state (either deregulation or patronage), I emphasize multiple state powers and the complexities of state-religion interplays in a specific sociopolitical context. It argues that the relation between state regulation and religious competition is contingent upon many factors including, but not limited to, the interplays between actors involved, sociocultural context, multiple and multilayered state powers. Second, state-regulated forms of patronage undertaken in Fujian demonstrate that the authority and legitimacy of the Chinese state has remained fortified through its multifunctional projects devoted to religious tourism, intra-religion competition and political unification with Taiwan, and that reconfigured governance has the potential to incorporate the “cultural nexus of power” through trade-offs between viability and autonomy. By surveying state presence in four Ciji temples, it also argues that the uneven revitalization of temple-based popular religion has in some cases affected and been affected by the stratification of state presence, and that the “partial institutionalization” of diffused religion has taken place, at least in certain temples, through the actions of party-state representatives and/or state policies aimed at channeling influential temples into modern state agendas. Third, both cultural festival and deity procession in Taiwan demonstrate that certain popular religion practices have been smoothly integrated into China’s political symbolism to “imagine” and “visualize” nation-state. Fourth, it suggests that an asymmetric symbiotic interrelationship between Chinese state and Taiwanese religious elites appeared in recent decades.